2008
DOI: 10.1007/s10338-008-0834-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Influence of Porosity Level on CFRP Composite Laminates Using Rayleigh Probe Waves

Abstract: It was found that a pitch-catch signal was more sensitive than normal incidence backwall echo of longitudinal wave to subtle flaw conditions in the composites (damages, fiber orientation, low level porosity, ply waviness, and cracks). Both the strength and stiffness depend on the fiber orientation and porosity volume in the composites. The porosity content of a composite structure is critical to the strength and performance of the structure in general. The depth of the sampling volume where the pitch-catch sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…More exactly, from the nondestructively obtained thermal diffusivity map, it is possible to gain information on the porosity distribution over the whole sample; whereas, on the contrary, the measure of density through the destructive volumetric method is just a local action regarding only a very small part of the sample. For a quantitative analysis, by calling Δ and Δ the variation of porosity and thermal diffusivity, respectively, we can introduce a parameter defined as = Δ Δ (7) which can also be regarded as a resolution measure of the employed method. It is possible to see that attains first a value of 5 until a porosity level of 4%, while it drops below 2 as the porosity increases towards 8%.…”
Section: Carbon Fiber Reinforcedmentioning
confidence: 99%
See 2 more Smart Citations
“…More exactly, from the nondestructively obtained thermal diffusivity map, it is possible to gain information on the porosity distribution over the whole sample; whereas, on the contrary, the measure of density through the destructive volumetric method is just a local action regarding only a very small part of the sample. For a quantitative analysis, by calling Δ and Δ the variation of porosity and thermal diffusivity, respectively, we can introduce a parameter defined as = Δ Δ (7) which can also be regarded as a resolution measure of the employed method. It is possible to see that attains first a value of 5 until a porosity level of 4%, while it drops below 2 as the porosity increases towards 8%.…”
Section: Carbon Fiber Reinforcedmentioning
confidence: 99%
“…Many techniques have been investigated for estimation of porosity in fiber reinforced composites [5][6][7][8][9][10][11][12][13]. Some are destructive like the acid digestion [5,10], which can supply information only by statistical inference and so has to be regarded as a reference rather than a quality assessment method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Several NDE methods that include radiography, acoustic techniques and infrared thermography are being used extensively for detection and evaluation of defects and damage in a composite material. [9][10][11][12][13][14][15][16][17][18] These techniques have shown versatility in evaluating the type and extent of defects/damages in a composite material. Perhaps less attention is dedicated to developing these techniques for assessing the environmental degradation of composite material that has its own set of challenges.…”
Section: Introductionmentioning
confidence: 99%
“…While delamination-type defects are explicitly visualized by ultrasonic echoes [1][2][3][4], distributions of minute pores, called porosity, need to be evaluated via overall changes in ultrasonic wave propagation characteristics. Foregoing studies have revealed that the porosity content of composites can be evaluated by measuring the attenuation of ultrasonic waves [5][6][7][8][9][10][11][12]. In practice, some threshold levels are preset for the height of ultrasonic echoes for each composite component to judge the porosity level on an empirical basis.…”
Section: Introductionmentioning
confidence: 99%